2020
DOI: 10.3390/medicina56050225
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Approach to the Temporomandibular Joint Osteoarthritis—Review of the Literature

Abstract: Background and objectives: There is an increasing number of patients applying for dental treatment who suffer from temporomandibular joint osteoarthritis (TMJOA). Osteoarthritis may be the cause of the pain in the area of temporomandibular joints, but its course may also be absolutely asymptomatic. The aim of this study was to present an interdisciplinary approach to TMJOA, including current diagnostics and treatment modalities on the basis of the available literature. Materials and Methods: PubMed and Scopus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 96 publications
(142 reference statements)
1
64
0
2
Order By: Relevance
“…Studies have assessed the prevalence of bone changes in the TMJ by using several parameters: different CBCT devices, application or not of image filters, voxels of different sizes, different image re-construction software, and different image assessment methods (Al-Ekrish et al, 2017;Choudhary et al, 2020;Derwich, Mitus-Kenig & Pawlowska, 2020;Hou et al, 2020;Miller et al, 2018;Oliveira et al, 2020;Sun et al, 2018;Urtane et al, 2018). Even so, it is possible to state that the majority of these studies found that faceting was the most prevalent change.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have assessed the prevalence of bone changes in the TMJ by using several parameters: different CBCT devices, application or not of image filters, voxels of different sizes, different image re-construction software, and different image assessment methods (Al-Ekrish et al, 2017;Choudhary et al, 2020;Derwich, Mitus-Kenig & Pawlowska, 2020;Hou et al, 2020;Miller et al, 2018;Oliveira et al, 2020;Sun et al, 2018;Urtane et al, 2018). Even so, it is possible to state that the majority of these studies found that faceting was the most prevalent change.…”
Section: Discussionmentioning
confidence: 99%
“…Patients diagnosed with TMJ reciprocal clicking require an interdisciplinary approach to the treatment, including physiotherapy and occlusal splint therapy, and could be offered innovative strategies in the field of conservative dentistry [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of TMJ OA requires an interdisciplinary approach [ 11 , 12 ]. There are three major aims of TMJ OA treatment: symptom relief including pain control, inactivation of the disease and finally retrieval of normal joint function [ 3 ].…”
Section: Treatment Of Tmj Oamentioning
confidence: 99%
“…There are three major aims of TMJ OA treatment: symptom relief including pain control, inactivation of the disease and finally retrieval of normal joint function [ 3 ]. Different methods of TMJ OA treatment have been grouped into several categories from the least to the most invasive procedures [ 11 , 13 ]. The abovementioned categories include: conservative treatment, including physiotherapy, occlusal splint therapy and pharmacotherapy; less invasive surgical procedures, including injections into the joint and arthrocentesis; and finally, invasive surgical procedures (arthroscopy and open joint surgery) [ 11 , 13 ].…”
Section: Treatment Of Tmj Oamentioning
confidence: 99%
See 1 more Smart Citation